Pengaruh Peran Koperasi Dalam Menumbuhkan Jiwa Kewirausahaan Pada Pengurus Dan Anggota Koperasi Sekolah SMAN Banjarmasin - Yanti, Yuli; Ratumbuysang, Monry Fraick Nicky Gillian; Rizky, Maulana; Suratno, Suratno (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This study aims to analyze the influence of the role of cooperatives in fostering the entrepreneurial spirit, especially in the administrators and members of school cooperatives in SMAN Banjarmasin City. The research method used is descriptive research with a quantitative approach. Samples were taken using purposive sampling technique as many as 163 people consisting of administrators and members of school cooperatives. Data collection techniques through observation, interviews and questionnaires to administrators and members of school cooperatives and by taking references from journals, books and other relevant sources. Instrument analysis in this study used the Rasch Model. Data analysis in this study was conducted using descriptive statistical analysis, classical assumption analysis, simple regression analysis and partial test (t-test). The results showed that there was a positive influence between the role of cooperatives on the entrepreneurial spirit of the administrators and members of school cooperatives in Banjarmasin City High School.